PREVALENCE OF ASTHMA, DENGUE, AND DIARRHEA AMONG CHILDREN IN SLUM COMMUNITIES IN CEBU CITY, PHILIPPINES - Alburo, Hemres M; Otadoy, Julie B (Journal of Agriculture and Technology Management, 2021)
Economic struggles have forced many families to live in slum areas in spite of the poor environmental condition, which often leads to many ailments. While conventional diseases had been controlled, ailments such as asthma, dengue, and diarrhea among other diseases have also developed due to varying aspects and states of pollution. This study aimed to determine the prevalence of asthma, dengue, and diarrhea affecting children in two slum communities in Cebu City, Philippines as a result of environmental degradation. The study was conducted in Inayawan landfill environs and along the downstream of Mahiga River. One hundred households were interviewed from each site using non-probability sampling. Results showed a higher prevalence of asthma and diarrhea among children below 18 years old in Inayawan with 23.86% and 19.65% than in Mahiga with 7.47% and 12.66%, respectively. Dengue cases were low in both sites with only 2.1% in Inayawan and 1.3% in Mahiga. About half of asthma and three-fourths of diarrheal cases in the study sites were only treated at home without medical advice. Educating these communities is of prime importance to facilitate treatment or even prevent these diseases from affecting their children.